2016
DOI: 10.1038/ijo.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins potentiate hypothalamic leptin/STAT3 signalling and Pomc gene expression in rats with diet-induced obesity

Abstract: Objective:Dietary obesity is usually linked with hypothalamic leptin resistance, in which the primary impact is an interference in the homeostatic control of body weight and appetite. Notably, proanthocyanidins (PACs), which are the most abundant phenolic compounds present in human diet, modulate adiposity and food intake. The aim of this study was to assess whether PACs could re-establish appropriate leptin signalling in both the hypothalamus and peripheral tissues.Design:Male Wistar rats were fed either a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 43 publications
2
48
0
1
Order By: Relevance
“…In comparison, the grape (Vitis vinifera) provides a more diverse source of OPCs, owing to the abundance of galloylated oligomers and type-A linked species (29). Until very recently, studies investigating the effectiveness of OPCs have typically applied the raw extract rather than the purified forms (9). The knowledge base surrounding OPCs mechanistic action is therefore modest and calls for expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the grape (Vitis vinifera) provides a more diverse source of OPCs, owing to the abundance of galloylated oligomers and type-A linked species (29). Until very recently, studies investigating the effectiveness of OPCs have typically applied the raw extract rather than the purified forms (9). The knowledge base surrounding OPCs mechanistic action is therefore modest and calls for expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Complex hydroxylation patterns, esterification, glycosylation, and multivariate stereoisomer formations of OPCs result in a wide range of bioactivities specific to individual moieties. A consequence of this complexity is that their separation is exceptionally challenging and thus, even to date, studies have used crude proanthocyanidin mixtures that have led to inconsistent, sometimes conflicting, conclusions (6)(7)(8)(9). It is therefore important to understand the health potential of homogenous OPCs before the synergetic therapeutic effect of OPCs, as demonstrated by TCM, Ayurveda, and European phytotherapies, can be fully understood.…”
mentioning
confidence: 99%
“…Sisley et al [95] have also shown that neuronal GLP-1 receptors mediate the anorexia effect of liraglutide (a persistent GLP-1 agonist). At the same time, GLP-1 activated POMC/CART neurons in the hypothalamus [96], indirectly inhibited neuropeptide Y/agouti-related peptide neurons through β-aminobutyric acid transmission, and together produced signals to reduce food intake, which indicated that GSPE affected the hypothalamic center [97], and then controlled food intake. However, the inhibiting effect of GSPE on food intake needs to be exerted at a specific dose without external pressure and calmness.…”
Section: Reduce Food Intakementioning
confidence: 98%
“…Previously, an increasing number of studies have demonstrated that leptin resistance was a major cause of obesity (65-67). The important reasons are the regulation of p-STaT3 and increased erS in the hypothalamus (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…For example, liu et al (72) reported that celastrol suppresses appetite, reduces body weight and ameliorates disorders of glucose and lipid metabolism through p-STaT3. ibars et al (68) reported that proanthocyanidins reduce appetite and weight by increasing phosphorylated STaT3. interestingly, the present study produced opposing results in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%